PATRIARCHY AND WOMEN SUBORDINATION IN ASSAMESE SOCIETY: AN ANALYSIS - Chetia, Lucky; Saikia, Dhrubajyoti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women are an integral part of society. A society is not complete without women. But women are always neglected and marginalised mainly under the system of patriarchy. Patriarchy is a social system where men occupy the pivotal position, political leadership, moral authority, special privilege and control of the property. Assam is not immune from this inhuman practice of the society. The patriarchy undermines the role of women in the society as well as the status of women. In view of this, the paper tries to highlight the following objectives (i) to understand the theoretical concept of patriarchy (ii) to examine the role of patriarchy in Assamese society. (iii) to explore the process institutionalization of patriarchy in Assam.